Serum Biomarkers for Inflammatory Bowel Disease - Chen, Peng; Zhou, Gaoshi; Lin, Jingxia; Li, Li; Zeng, Zhirong; Chen, Minhu; Zhang, Shenghong (Frontiers in Medicine, 2020)
Background: Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is a chronic, inflammatory disorder of the gastrointestinal tract. As the novel therapeutic goal and biologicals are widely recognized, accurate assessment of disease and prediction of therapeutic response have become a crucial challenge in clinical practice. Also, because of the continuously rising incidence, convenient and economical methods of diagnosis and clinical assessment is urgently needed. Recently, serum biomarkers have made a great progress and become a focus in IBD study since they are non-invasive, convenient, and relatively inexpensive compared to using markers in biopsy tissue, stool, breath, and other body fluids. Aims: To review the available data on serological biomarkers for IBD. Methods: We searched PubMed using pre-defined key words on relevant literatures of serum biomarkers regarding diagnosis, evaluation of therapeutic efficacy, surveillance of disease activity, and assessment of prognosis for IBD. Results: We reviewed serological biomarkers that are well-established and widely-used (e.g., C-reactive protein), newly discovered biomarkers (e.g., cytokines, antibodies, non-coding RNAs), and also recently advance in serological biomarkers (e.g., metabolomics, proteomics) that are used in different aspects of IBD management. Conclusions: With such a wealth of researches, there is still no ideal serum biomarkers for IBD to date. Serum profiling and non-coding RNAs are just started to blossom but reveal great promise for future clinical practice. Combining different biomarkers can be valuable in improving performance of disease evaluation.